The impact of adult children rural–urban migration on left-behind parents' health: Evidence from China - Zhang, Chi; Lyu, Kaiyu; Cheng, Xiaoyu; Zhang, Chongshang (Frontiers in Public Health, 2022)
Population aging and rural-urban migration have posed challenges to the elderly support system in developing countries that lack social safety net and services. Given that there is no consistent conclusion in the literature on whether the adult children’s internal migration can improve or impair their left-behind parents’ health, and little is known about the effect mechanisms. This paper investigates the comprehensive impact of adult children migration on the health of their parents in rural China by analyzing the income effect and time allocation effect. The empirical analysis uses the rural sample of China Health and Retirement Longitudinal Study (CHARLS) in 2013, 2015 and 2018. We found that children migration can improve parents’ physical health, mainly thanks to the income effect. The analysis of the mechanism found that although the income effect has a positive effect on parents’ health, but the time allocation effect has a negative effect on parents’ health because of the lack of care and increased working hours of parents. Our findings suggest that providing social care services and enhancing intergenerational communication can be practical strategies to mitigate the negative effect of children’s migration to rural left-behind elderly parents.